An analysis of academic staff service scheme of selected private universities in Malaysia - Mhd. Sarif, Suhaimi (2010)
This study has analyzed overall, qualitative characteristics of service scheme of selected private universities in Malaysia. Awareness of service scheme of players in the same industry could help a private university position itself from staff recruitment and retention perspectives. With such knowledge, private universities could develop strategies to attract resourceful academic and administrative staff. The study emphasizes findings from survey questionnaire and personal interviews. It de-emphasizes literature review. The most predominant method employed in this study was personal interview. Data gathering proved extremely difficult due to rigidity and confidentiality of informational disclosure. Conclusion, limitation of the study, managerial implications, and future research directions are highlighted.